Construction for Arisan Ukhuwah Basic Profit and Loss Sharing KSPPS Ya Umi Maziyah Assa’adah - Eni Kusrini (CV. Rayyan Dwi Bharata, 2023)
Arisan Ukhuwah Profit and Loss Sharing is economic sharia activity free from the element s of usury. This arisan make a profitable contribution for UMKM perpetrator. Arisan management system use sharia economic. This research implemented in KSPPS Ya Umi Maziyah Assa’adah. This research using a descriptive qualitative approach. Research results show that arisan participants pay one hundred thousand rupiah every month until twenty four months. During the arisan payment period, KSPPS Ya Umi Maziyah Assa’adah manage the arisan money to activities of entrepreneurial. After that arisan drawn together. The money will be handed over after twenty four months of payments. Profit and loss sharing to arisan participants as much 14% and KSPPS Ya Umi Maziyah Assa’adah 86%. Besides that arisan participants get a raffle prize from KSPPS Ya Umi Maziyah Assa’adah. This arisan activities provide and advantage for arisan participants and entrepreneurial surrounding.